2018
DOI: 10.1016/j.stem.2018.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Phospho-regulation of ATOH1 Is Required for Plasticity of Secretory Progenitors and Tissue Regeneration

Abstract: SummaryThe intestinal epithelium is largely maintained by self-renewing stem cells but with apparently committed progenitors also contributing, particularly following tissue damage. However, the mechanism of, and requirement for, progenitor plasticity in mediating pathological response remain unknown. Here we show that phosphorylation of the transcription factor Atoh1 is required for both the contribution of secretory progenitors to the stem cell pool and for a robust regenerative response. As confirmed by lin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
61
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 37 publications
6
61
1
Order By: Relevance
“…Upon injury, however, both colonic and intestinal Atoh1 + cells expand to renew the epithelium, consistent with plasticity required for crypt regeneration. Our observations are consistent with the recent findings reported by two other groups demonstrating that Atoh1 + secretory cells are able to contribute to colonic regeneration post-colitis (Ishibashi et al, 2018;Tomic et al, 2018). Thus, a subset of Atoh1 + cells in the colon can renew the epithelium during normal homeostasis, whereas in the small intestine, Atoh1 + cells behave similarly to intestinal Dll1 + progenitors cells that are short-lived and only lineage trace upon epithelial injury (van Es et al, 2012).…”
supporting
confidence: 93%
See 2 more Smart Citations
“…Upon injury, however, both colonic and intestinal Atoh1 + cells expand to renew the epithelium, consistent with plasticity required for crypt regeneration. Our observations are consistent with the recent findings reported by two other groups demonstrating that Atoh1 + secretory cells are able to contribute to colonic regeneration post-colitis (Ishibashi et al, 2018;Tomic et al, 2018). Thus, a subset of Atoh1 + cells in the colon can renew the epithelium during normal homeostasis, whereas in the small intestine, Atoh1 + cells behave similarly to intestinal Dll1 + progenitors cells that are short-lived and only lineage trace upon epithelial injury (van Es et al, 2012).…”
supporting
confidence: 93%
“…Complementing the recent findings showing that phosphorylation of ATOH1 regulates the plasticity of secretory progenitors (Tomic et al, 2018), we found that renewal by Atoh1 + cells is independent of Lgr5 + stem cells and that Atoh1 + cells are multipotent in terms of their renewal capacity. This is demonstrated by their ability to give rise to colonic organoids in vitro, as well as to lineage trace in vivo in the absence of Lgr5 + cells by DT ablation during regeneration.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…Many studies have suggested that phosphorylation of ATOH1 affects its protein stability (Aragaki et al, 2008;Cheng et al, 2016;Forget et al, 2014;Klisch et al, 2017;Tomic et al, 2018;Tsuchiya et al, 2007;Xie et al, 2017). Among previously reported phosphorylation sites, S52, S56, tyrosine (Y)78, S193, S328, S334 and S339 of mouse ATOH1 are believed to participate in the protein stability.…”
Section: Canonical Wnt Signaling Controls the Dynamic Expressions Of mentioning
confidence: 99%
“…It was previously suggested that CCND1 and CDK4 are involved in phosphorylation of ATOH1 in HEK293T cells (Tomic et al, 2018). However, it remained unclear whether CCND1/CDK4 directly phosphorylates ATOH1 or whether ATOH1 phosphorylation by CCND1/CDK4 participates in stabilization of ATOH1.…”
Section: Introductionmentioning
confidence: 99%